COMMUNICATION AND MANAGEMENT STRATEGIES IN FUNDRAISING FUNDS AT SAHABAT YATIM MEDAN BRANCH - Hajar, Siti; Ritonga, Elfi Yanti (Al-Mubin, 2025)
Every organizational institution needs a communication strategy to attract public attention. On the management side, the institution implements a program planning system based on religious moments, transparent financial reporting, annual audits by BPK and sharia audits, as well as a trust-based donor relations system and direct involvement. This study aims to analyze communication and management strategies in the fundraising process at Sahabat Yatim Medan Branch, a social institution that focuses on the empowerment of orphans and poor people. Using a descriptive qualitative approach, data was collected through observation, in-depth interviews, and documentation studies. The results of the study show that the strategies used by this institution are based on storytelling strategies, social education, and optimization of social media such as Instagram, WhatsApp, and TikTok to reach young donors and families. The main obstacle faced is maintaining public trust amid increasing saturation of social campaigns and embezzlement scandals by other philanthropic institutions. This study concludes that the synergy between empathetic communication strategies and professional management is the key to sustainable fundraising success. These findings can serve as a model of practice for other social institutions in building public trust and improving fundraising effectiveness